2006
DOI: 10.1007/s10535-006-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine contents, ethylene synthesis, and BrACO2 expression during turnip germination

Abstract: Contents of total free [PA(S)] and conjugated polyamines [PA(SH), PA(PH)] were higher in turnip (Brassica rapa L. cv. Rapa) seeds during imbibition (0 -36 h) and radicle protrusion (36 -48 h) than during the further growth (10 d).Ethylene production was activated with the protrusion, reaching a maximum at the second day of germination and dropping afterwards. The application of ethrel accelerated radicle emergence but the direct intervention of ethylene in the breaking of the seed coat was not clear from the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Spd content (free as well as other forms) was higher throughout the germination process (imbibition and metabolism activation phases) in both primed and unprimed variants as compared to Put and Spm ( Supplementary Table S1 ). These results are in line with those observed in Arabidopsis thaliana , Malus domestica , Cedrela fissilis , and sweet corn, where Spd content was also higher than other PAs [ 37 , 38 , 39 , 40 ]. In Arabidopsis , the addition of exogenous Put (but not Spd or Spm) resulted in the inhibition of germination [ 41 ], which suggests the function of Put in the regulation of germination.…”
Section: Discussionsupporting
confidence: 91%
“…Spd content (free as well as other forms) was higher throughout the germination process (imbibition and metabolism activation phases) in both primed and unprimed variants as compared to Put and Spm ( Supplementary Table S1 ). These results are in line with those observed in Arabidopsis thaliana , Malus domestica , Cedrela fissilis , and sweet corn, where Spd content was also higher than other PAs [ 37 , 38 , 39 , 40 ]. In Arabidopsis , the addition of exogenous Put (but not Spd or Spm) resulted in the inhibition of germination [ 41 ], which suggests the function of Put in the regulation of germination.…”
Section: Discussionsupporting
confidence: 91%
“…Seed dormancy in A. platanoides (Szczotka and Lewandowska, 1989) was broken by exogenous application of Spm. Total amounts of free and conjugated PAs increased during imbibition and decreased from radicle protrusion onwards in chick-pea seeds (Gallardo et al, 1992), as well as Brassica rapa (Puga-Hermida et al, 2006) and Picea abies (Gemperlová et al, 2009). A recent study demonstrated that inhibition of an intermediate compound at the methionine cycle alters PA levels, and impairs seedling growth and reproduction in arabidopsis (Bürstenbinder et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…S-Adenosylmethionine, a substrate for ACS activity is also a component of other important physiological pathways, e.g., polyamine biosynthesis (Puga-Hermida et al 2006;Matilla and Matilla-Vazquez 2008). Activity of enzymes responsible for methionine and SAM synthesis in seeds was detected mainly during terminal phase of germination deWned by radical protrusion (Gallardo et al 2000).…”
Section: Discussionmentioning
confidence: 99%